Characterization of Legal Claims Involving Patients with Pyoderma Gangrenosum. (27th November 2022) - Pfeifer, Hailey J.; Orfaly, Victoria E.; Rick, Jonathan W.; Damitio, Christopher; Ortega Loayza, Alex G.
ABSTRACT: OBJECTIVE: To review the litigation literature related to patients with pyoderma gangrenosum (PG) to characterize the legal issues they face. DATA SOURCES: Data sources include law databases Casetext and Lexis Nexis. STUDY SELECTION: All disability and medical liability claims directly involving patients with PG were included. DATA EXTRACTION: Data extraction came directly from Casetext and Lexis Nexis. All cases extracted came from September 1965 to December 2020. This resulted in 32 cases, 18 of which were excluded because they did not mention the plaintiff having a diagnosis of PG (n = 14). DATA SYNTHESIS: The review found a total of six medical liability cases in which adverse health outcomes were reported, including prolonged suffering (2/6 cases), unnecessary treatments or procedures (2/6), exacerbation of disease (1/6 cases), and permanent scarring (1/6 cases). Despite this, two plaintiffs won their case and only one of them received any monetary award. Similarly, of the eight disability claims in the review, four were ruled in the favor of the plaintiffs and only two resulted in immediate awarding of benefits. Half of medical liability cases occurred in correctional facilities after the denial of appropriate care. CONCLUSIONS: The findings demonstrate a need for access to specialty care in incarcerated populations. Cases that occurred in a hospital setting also stress the importance of initiatives such as telemedicine to efficiently increase access to care in a cost-effective manner. Further, PG has been recognized as a severe impairment in disability claims despite patients being denied because they were deemed able to perform other work.